2022
DOI: 10.1080/0144929x.2022.2027013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of determinants and consequences of bystander interventions in online hate and cyberbullying among adults

Abstract: Despite the substantial amount of literature concerning adolescent bystanders of online hate and cyberbullying, relatively little attention has been devoted to studying the same issue in adults. Similarly, the determinants of the effectiveness of different messages to support the victims or counter hate have also been understudied. The existing pieces of empirical research on these topics remained scattered and no systematic review was performed to check if there are any patterns with regard to determinants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 98 publications
1
25
0
Order By: Relevance
“…Today the easy and instant access of youths to new technologies has highlighted the phenomenon of cyberbullying as a common online risk behavior among them who intentionally use electronic devices to harm others (Smith et al, 2008), with a negative impact at both the socio-emotional and the educational level (Rudnicki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Today the easy and instant access of youths to new technologies has highlighted the phenomenon of cyberbullying as a common online risk behavior among them who intentionally use electronic devices to harm others (Smith et al, 2008), with a negative impact at both the socio-emotional and the educational level (Rudnicki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The current findings align with previous studies demonstrating that the severity of incidents as a factor has an important impact on bystander intention to intervene. 18 , 19 , 23 Compared with traditional bullying, cyberbullying on SNSs has a variety of forms and types, and thus, the severity varies considerably between cyberbullying incidents. 36 Bystanders assess the severity of the incident.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the severity of cyberbullying incidents is one of the important factors. 18 , 19 The higher the severity of incidents, the stronger the intention of bystanders to intervene. 20 , 21 However, it is not clear how the severity of cyberbullying incidents affects bystander intention to intervene, and few studies have explored the boundary conditions for the effect produced by the severity of incidents.…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies show that aggressive peer behaviors occur more frequently when perpetrators are not held accountable for their behaviors (when they think their actions remain confidential from people outside of their peer group) [39][40][41]. A recent systematic review on the determinants and consequences of bystander interventions in cyberbullying found that perceived accountability boosts the likelihood that people will refrain from conforming to cyber aggression and instead help victims [42]. Adolescents who feel unaccountable to others typically perceive little risk of potential adult intervention or punishment for their behaviors [2,43].…”
Section: Empirical Research On Conformity To Cyber Aggressionmentioning
confidence: 99%